Uji Efektivitas Pestisida terhadap Beberapa Patogen Penyebab Penyakit Penting pada Buah Naga (Hylocereus sp.) secara In Vitro - Ani Widiastuti; Wahyu Agustina; Arif Wibowo; Christanti Sumardiyono (Jurnal Perlindungan Tanaman Indonesia, 2011)
Problem caused by pathogen in Dragon Fruit (Hylocereus sp.) cultivation became very important because it decreased significantly the quantity and quality of the fruit production. This study aims to determine the effectiveness of some pesticides against pathogens that cause diseases of dragon fruit in several plantations in the DIY (Sleman and Kulon Progo) and Central Java (Magelang and Batang). Test of fungicide effectiveness was done in vitro on PDA medium (potato dextrose agar) by poisoned food technique. The fungicides were mancozeb 80 %, methyl tiofanat 70 %, copper hydroxide 80 %, chlorotalonil 75 %, mancozeb 64 % + metalaxyl 4 %, mancozeb karbendazim 73.8 % + 6.8 %,benomyl 50 % at a concentration of 1g/L. The bactericides used were streptomycin sulfate 20 % and oxytetracycline 150 AL with each concentration of 1 g/L and 1 mL /L. The results showed that benomyl 50 % was the most effective fungicide to suppress the growth of Fusarium sp. (brown spot), Colletotrichum sp. (anthracnose) and Pestalotiopsis sp. (scab), followed by mancozeb 73.8 % +karbendazim 6.8 % and 73.8 % mancozeb. Bactericide which was able to suppress the growth of Erwinia sp. (stem rot) was streptomycin sulfate 20 %.